Etude electromyographique des muscles trapezius (partie moyenne) et rhomboideus major sousmis a tension isometrique - De Freitas, V.; Vitti, M. (My University, 1981)
The participation of the trapezius (middle portion) and rhomboideus major muscles submitted to an isometric tension (holding downward dumbells of 11, 15 and 19 kg) was analysed in 40 young adult male vounteers. A 2 channel TECA TE4 electromyograph connected with single coaxial needle electrodes was used. In the initial phase of the test, holding downward, generally the trapezius and rhomboideus major muscles showed activity and no activity, respectively. In the cases where activity was present during the downward positions it was reduced gradually until complete rest.
Electromyographic study of trapezius (middle portion) and rhomboideus major muscles submitted to an isometric tension
Keywords: electromyography; muscle; muscle isometric contraction; normal human; rhomboideus major muscle; trapezius muscle; action potential; adult; back; exercise; human; male; physiology; Action Potentials; Adult; Back; Electromyography; English Abstract; Exertion; Human; Isometric Contraction; Male; Muscles